PENATAAN KELEMBAGAAN BUMDES BERBASIS PARIWISATA - Muchamad Zaenuri; Muhammad Eko Atmojo; Muhammad Iqbal (Universitas Sanata Dharma, 2019)
The Main Problem In Bumdes Management In Donoharjo Village Is The Lack Of Optimal Management Of The Organization Following The Principles Of Good Organizational Governance. Specifically, Issues In The Management Of Bumdes In Donoharjo Village Include 1) The Absence Of A Standard Reference Or Guideline For Professionally Managing The Jetis Suruh Reservoir; 2) There Is No Clear Organizational Structure; 3) The Lack Of Basic Tasks And Functions For Managers; 4) There Is No Sop To Follow Up On Various Work Programs Related To The Jetis Suruh Dam; 5) The Unavailability Of Human Resources Capable Of Moving Bumdes Organizations That Refer To Good Governance. Based On The Identification Of The Problem, The Following Activities Were Carried Out: Training On The Preparation Of Governance Guidelines, Focus Group Discussion On The Formation Of Auth And Jobs Descriptive, Fgd On The Arrangement Of Governance Implementation Materials, 5. Training For Tour Guides And Management Assistance. The Results Of These Activities Make The Governance Of Bumdes Desa Donoharjo More Effective And Efficient.